Anthracyclines and the risk of arrhythmias: A systematic review and meta-analysis - Dean, Yomna E.; Dahshan, Hazem; Motawea, Karam R.; Khalifa, Ziad; Tanas, Yousef; Rakha, Ibrahim; Hasan, Walaa; Kishk, Mohamed; Mahmoud, Alaa; Elsayed, Ahmed; Abdelkader, Omar; Tokunaga, Akiko; et al. (Medicine, 2023)
Background: There have been controversial findings from recent studies regarding anthracyclines use and the subsequent risk of arrhythmias. This study aimed to evaluate the existing evidence of the risk of arrhythmias in patients treated with anthracyclines. Methods: PubMed, Scopus, and Web of Science databases were searched up to April 2022 using keywords such as "anthracycline" and "arrhythmia." Dichotomous data were presented as relative risk (RR) and confidence interval (CI), while continuous data were presented as mean difference (MD) and CI. Revman software version 5.4 was used for the analysis. Results: Thirteen studies were included with a total of 26891 subjects. Pooled analysis showed that anthracyclines therapy was significantly associated with a higher risk of arrhythmia (RR: 1.58; 95% CI: 1.41-1.76; P < .00001), ST segment and T wave abnormalities (RR: 1.73, 95% CI: 1.18-2.55, P = .005), conduction abnormalities and AV block (RR = 1.86, 95% CI = 1.06-3.25, P = .03), and tachycardia (RR: 1.736, 95% CI: 1.11-2.69, P = .02). Further analyses of the associations between anthracyclines and atrial flutter (RR = 1.30, 95% CI = 0.29-5.89, P = .74), atrial ectopic beats (RR: 1.27, 95% CI: 0.78-2.05, P = .34), and ventricular ectopic beats (RR: 0.93, 95% CI: 0.53-1.65, P = .81) showed no statistically significant results. Higher doses of anthracycline were associated with a higher risk of arrhythmias (RR: 1.49; 95% CI: 1.08-2.05; P = .02) compared to the lower doses (RR: 1.36; 95% CI: 1.00-1.85; P = .05). Newer generations of Anthracycline maintained the arrhythmogenic properties of previous generations, such as Doxorubicin. Conclusion: Anthracyclines therapy was significantly associated with an increased risk of arrhythmias. Accordingly, Patients treated with anthracyclines should be screened for ECG abnormalities and these drugs should be avoided in patients susceptible to arrhythmia. The potential benefit of the administration of prophylactic anti-fibrotic and anti-arrhythmic drugs should also be explored.